ANALISIS MOTIVASI DAN KEDISIPLINAN KERJA KARYAWAN PT LION AIR DISTRIK PONTIANAK - B31109024, DICKY JUNAIDI (Jurnal Manajemen Update, 2016)
Globalization that hit today's economy requires companies to be more effective and efficient in conducting any business activity. As an illustration, this analysis is applied to the employees of PT. Lion Air District Pontianak by taking the number of employees by 75 people. Study discusses how companies PT. Lion Air District Pontianak in motivating its employees work, and knowing the perception of employees of PT. Lion Air District Pontianak to policies issued by the company. This study uses descriptive qualitative research. Results of this study found that According to the employees of PT. Lion Air District Pontianak, employer participation in the delivery of the policy will have the added value of all the employees. With the participation would make employees feel more considered by the company. According to some of the subordinate employees of PT. Lion Air District Pontianak, companies less care of its employees in terms of overtime policies. The subordinate employees also looked superiors less rapidly in response to a request made a few employees who are protesting. Keywords: Motivating, Perception, Descriptive qualitative.